Patient-Reported Outcomes for Pediatric Adherence and Self-Management: A Systematic Review. (17th December 2019) - Plevinsky, Jill M; Gutierrez-Colina, Ana M; Carmody, Julia K; Hommel, Kevin A; Crosby, Lori E; McGrady, Meghan E; Pai, Ahna L H; Ramsey, Rachelle R; Modi, Avani C
Abstract: Objective: Treatment adherence is approximately 50% across pediatric conditions. Patient-reported outcomes (PROs) are the most common method of measuring adherence and self-management across research and clinical contexts. The aim of this systematic review is to evaluate adherence and self-management PROs, including measures of adherence behaviors, adherence barriers, disease management skills, and treatment responsibility. Methods: Following PRISMA guidelines for systematic reviews, literature searches were performed. Measures meeting inclusion/exclusion criteria were evaluated using Hunsley and Mash's (2018) criteria for evidence-based assessment across several domains (e.g., internal consistency, interrater reliability, test–retest reliability, content validity, construct validity, validity generalization, treatment sensitivity, and clinical utility). Rating categories were adapted for the present study to include the original categories of adequate, good, and excellent, as well as an additional category of below adequate. Results: After screening 172 articles, 50 PROs across a variety of pediatric conditions were reviewed and evaluated. Most measures demonstrated at least adequate content validity ( n = 44), internal consistency ( n = 34), and validity generalization ( n = 45). Findings were mixed regarding interrater reliability, test–retest reliability, and treatment sensitivity. Less than half of the measures ( n = 22) exhibited adequate, good, or excellent construct validity. Conclusions: Although use of adherence and self-management PROs is widespread across several pediatric conditions, few PROs achieved good or excellent ratings based on rigorous psychometric standards. Validation and replication studies with larger, more diverse samples are needed. Future research should consider the use of emerging technologies to enhance the feasibility of broad implementation.